Successful endovascular exclusion of Mycobacterium bovis mycotic aneurysm following intravesical bacille Calmette–Guerin therapy. Issue 10 (27th October 2022) - Cook, Victoria; Singla, Animesh A; Herlihy, David; Mohabbat, Walid; Fisher, Charles; Puttaswamy, Vikram
Abstract: Bacille Calmette–Guerin (BCG) is a live-attenuated strain of Mycobacterium bovis . It is routinely used in the treatment of early-stage transitional cell carcinoma. The development of mycotic aneurysm in the context of prior intra-vesical BCG treatment has not been reported. This case demonstrates a rare but potentially catastrophic vascular complication of BCG. A high index of suspicion is required for any patient presenting with new aneurysmal disease in the context of previous BCG therapy. The value of endovascular surgery as a bridge to definitive surgical repair and diagnostic considerations is discussed.